E-comic geneius: Contextual genetics learning media to enhance cognitive learning outcomes - Firdaus, Zahra; Zubaidah, Siti; Fahmi, M Iqbal Najib; Setiawan, Deny; Chang, Chun-Yen (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Understanding genetics remains a challenge for high school students due to the abstract nature of the content and its limited connection to everyday experiences. Traditional teaching methods often rely on memorization without promoting meaningful conceptual understanding. This study aims to develop contextual genetics learning media in the form of an electronic comic (e-comic) titled “Geneius”, and to test its validity, practicality, and effectiveness in improving students’ cognitive learning outcomes. The e-comic integrates fictional storylines with genetics concepts based on everyday situations to enhance conceptual understanding. This research employed the Lee and Owens multimedia-based instructional design model, consisting of analysis, design, development, implementation, and evaluation stages. The quasi-experimental design used was a pretest-posttest control group design involving 60 high school students. The effectiveness of the media was tested using 10 cognitive questions (6 HOTS and 4 LOTS), and data were analyzed with a One-way ANCOVA. The results showed that the material and media validation scores were 100% and 95% (very valid), respectively, and the practicality of the media was 92.5% (very practical). Although the ANCOVA significance value was 0.018, an increase was observed in students’ HOTS performance. These findings indicate that the “Geneius” e-comic is a feasible and engaging alternative to support genetics learning and improve cognitive outcomes. The study recommends the implementation of interactive, contextual digital media in genetics education.